Pengaruh Produk Halal Non-Label Terhadap Perceived Quality dan Minat Beli Makanan Ringan di Mataram - Asdiansyuri, Ulfiyani; Octavia, Yusi Faizhatul (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2018)
This research aims to determine the influence of unlabeled halal products through perceived quality on buying interest of snack products in Mataram city. This type of research includes associative research. The population used was snack product customers in Mataram city, while the number of samples taken was 100 respondents using purposive sampling technique. Data was collected using a questionnaire. The data has been collected then analyzed using SEM (Structure Equation Model) analysis, by utilizing the AMOS application program. Data processing results show that unlabeled halal products variable have a positive and significant influence to perceived quality and buying interest, while perceived quality has not significant influence on buying interest. This means that perceived quality variables are not proven to mediate the influence of unlabeled halal products on buying interest. This is because perceived quality which is an intervening variable has not significant influence on buying interest.